A Fuzzy Set Based Approach for Rating Bias - Li, Mingming; Dai, Jiao; Zhu, Fuqing; Zang, Liangjun; Hu, Songlin; Han, Jizhong (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
In recommender systems, the user uncertain preference results in unexpected ratings. This paper makes an initial attempt in integrating the influence of user uncertain degree into the matrix factorization framework. Specifically, a fuzzy set of like for each user is defined, and the membership function is utilized to measure the degree of an item belonging to the fuzzy set. Furthermore, to enhance the computational effect on sparse matrix, the uncertain preference is formulated as a side-information for fusion. Experimental results on three real-world datasets show that the proposed approach produces stable improvements compared with others.